Steroidogenesis in the NCI-H295 Cell Line Model is Strongly Affected By Culture Conditions and Substrain - Kurlbaum, Max; Sbiera, Silviu; Kendl, Sabine; Martin Fassnacht, M.; Kroiss, Matthias (Experimental and Clinical Endocrinology & Diabetes, 2020)
Context NCI-H295 cells are the most widely used model for adrenal steroidogenesis and adrenocortical carcinoma and have been used for decades in laboratories worldwide. However, reported steroidogenic properties differ considerably.Objective To evaluate heterogeneity of steroidogenesis among NCI-H295 cell strains, clarify the influence of culture media and test response to inhibitors of steroidogenesis by using liquid chromatography tandem mass spectrometry (LC-MS/MS).Methods NCI-H295 cells were obtained from two cell banks and cultivated in different media. An LC-MS/MS-based panel analysis of thirteen steroids was adapted for cell culture supernatant. Cells were treated with metyrapone, abiraterone and mitotane.Results Mineralocorticoid synthesis was strongly affected by passaging as reflected by reduction of aldosterone secretion from 0.158±0.006 to 0.017±0.001 µg/106 cells (p<0.05). Relevant differences were also found for cells from two vendors in terms of aldosterone secretion (0.180±0.001 vs. 0.09±0.002 µg/106 cells, p<0.05). Selection of medium strongly impacted on cortisol secretion with>4-fold difference (40.6±5.5 vs. 182.1±23 µg/106 cells) and reflected differential activation of the glucocorticoid pathway. Exposure to abiraterone, metyrapone and mitotane resulted in characteristic steroidogenic profiles consistent with known mechanism of drug action with considerable differences in metabolites upstream of the blocked enzyme.Conclusion We demonstrate that steroid hormone secretion in NCI-H295 cells is strongly affected by the individual strain, passage and growing conditions. These factors should be taken into account in the evaluation of experiments analyzing steroid parameters directly or as surrogate parameters of cell viability.
Keywords: Steroid hormones; glucocorticoids; androgens; adrenocortical carcinoma; cell culture